10. Visual electrophysiology. A good friend can help you in need. Issue 4 (April 2016) - Tozzi, M.C.; Silipo, S.; Monaco, S.; Bertolasi, L.
Abstract : Scotopic and photopic full field-Electroretinogram (ERG), pattern electroretinogram (PERG) and visual evoked potential (VEP) are stimulating and recording methods to evaluate the functionality of the different layers of retina and of the visual pathway from retina to visual cortex of the brain. Visual electrophysiology is a useful diagnostic tool which aids in cases of unexplained visual loss if the clinician is well-versed in this techniques. Furthermore the new ocular imaging tests such us OCT give only morphological informations about retina and the head of optic nerve that need functional correlations with the symptoms of the patient. We review the diagnostic protocol for neurophysiological assessment of afferent visual system performed in our lab and describe normative data from 30 healthy subjects.